Relationship between learning motivation and student achievement of Bina Nusantara University - Octafiani Hartawan, Ferren; Lawrence, Cindy; Chrisanto, Agustinus Yovian; Cornelius, Louis; Kurniawan, David; Surya, William; Jonathan, Darren; Briana Soetanto, Cindy (Journal of Economics and Business Letters, 2021)
Learning motivation is a motivational drive from a person to learn a material. There are factors that influence learning motivation such as lesson materials and teacher attitudes when teaching, family and the environment of friendship. When someone has a good interest in learning, he will produce good results. This result is called the achievement result which is the result of working on an exam or task. Achievement results are measured by numbers and are academic in nature. The higher the learning motivation possessed by a person, the higher the achievement results he gets and vice versa.